2018
DOI: 10.1103/physreve.98.012701
|View full text |Cite
|
Sign up to set email alerts
|

Lifting ordered surfaces: Ellipsoidal nematic shells

Abstract: When a material surface is functionalized so as to acquire some type of order, functionalization of which soft condensed matter systems have recently provided many interesting examples, the modeler faces an alternative. Either the order is described on the curved, physical surface where it belongs, or it is described on a flat surface that is unrolled as preimage of the physical surface under a suitable height function. This paper applies a general method that pursues the latter avenue by lifting whatever orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…For temperatures where the nematic phase is well established, our results revealed that liquid crystal molecules exhibit an azimuthal alignment in the absence of an external field, with a pair of half-strength defects at each spherical cup. This behavior contrasts with previous reports for nematic shells with an anisotropic shape, 22,24,27 such as spherocylindrical and prolate ellipsoidal geometries, where the molecular alignment is along the meridian. When a transversal electric field is applied, we verified that the vortex-like configuration is replaced by a molecular alignment along the field direction.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For temperatures where the nematic phase is well established, our results revealed that liquid crystal molecules exhibit an azimuthal alignment in the absence of an external field, with a pair of half-strength defects at each spherical cup. This behavior contrasts with previous reports for nematic shells with an anisotropic shape, 22,24,27 such as spherocylindrical and prolate ellipsoidal geometries, where the molecular alignment is along the meridian. When a transversal electric field is applied, we verified that the vortex-like configuration is replaced by a molecular alignment along the field direction.…”
Section: Discussioncontrasting
confidence: 99%
“…[18][19][20] Recently, several studies investigated geometrical-induced defects in nematic shells presenting an anisotropic shape. [21][22][23][24][25][26] In particular, symmetry breaking causes the curvature of liquid crystal shells to vary, which tends to modify both the arrangement 22,23 and number of valence centers. 12,27 A prominent example is a hybrid shell consisting of a liquid crystal droplet with an elongated nanoparticle in the central core.…”
Section: Introductionmentioning
confidence: 99%